Nitrogen doses in the development of DiscoveryTM Bermudagrass during winter - Prates, Adrielle Rodrigues; dos Santos, Patrick Luan Ferreira; do Nascimento, Matheus Vinícios Leal; Costa, João Victor; Silva, Philippe Solano Toledo; Villas Bôas, Roberto Lyra (Ornamental Horticulture, 2020)
DiscoveryTM bermudagrass has been used in ornamental and sporty low-traffic turfgrass, due to its intense green coloring and slow growth, as an alternative in the search to reduce maintenance costs, such as cutting and nitrogen fertilization. However, little is known about fertilization recommendations in winter seasons, especially nitrogen fertilization. In this sense, the objective was to evaluate different doses of N in the development of bermudagrass DiscoveryTM in winter. The experiment was carried out during the winter, in an area with DiscoveryTM lawn already implemented. The design was entirely causalized, with 5 doses of N (0, 15, 30, 45 and 60 g N m-2) through the application of urea, with four repetitions, using 20% of the doses, according to crop requirement for winter, in a single application. The evaluated parameters were green color index (GCI), (Scout CM-1000 and Scout TCM 500), height, dry mass, traction and analysis by digital image of the lawn. It was observed that with the increase of N doses there was an increase in biometric assessments, however the analysis by digital image showed uneven results, and the traction of the lawn did not differ between treatments. Larger doses provided a better visual aspect of the lawn, but for the economic aspect, it is concluded that the use of 20% of the doses between 30 and 40 g N m-2, applied only once during the winter, is more recommended for the development of the DiscoveryTM bermudagrass.